Challenges of the New Partnership for Africa's Development (NEDAD) : a case analysis of the African Peer Review Mechanism (APRM) - Kuye, Jerry O. (University of Pretoria, 2013)
Thesis (PhD (Public Affairs))--University of Pretoria, 2008.